2003
DOI: 10.1002/eji.200324429
|View full text |Cite
|
Sign up to set email alerts
|

Dominance of CCL22 over CCL17 in induction of chemokine receptor CCR4 desensitization and internalization on human Th2 cells

Abstract: Chemokines and their receptors play a pivotal role in controlling T cell trafficking in immunity and inflammation. Two chemokines, CCL17 and CCL22, activate the chemokine receptor CCR4, expressed on functionally distinct subsets of T cells: cutaneous leukocyteassociated antigen (CLA) + skin-homing, T helper (Th) 2, and CD25 + T suppressor cells. Here, we compared the ability of CCL17 and CCL22 to promote CCR4 internalization as a mechanism of regulation of receptor function on human Th2 cells. We report that C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
90
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(105 citation statements)
references
References 52 publications
11
90
3
Order By: Relevance
“…In addition, there was increased expression of the chemokine CCL17 (Figures 5b and 6d), the ligand of CCR4, which could recruit CD4 þ Th2 into the lesional sites. 15,16 Therefore, these data collectively indicated that this modified model resembled the Th2-predominant pattern in SSc.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In addition, there was increased expression of the chemokine CCL17 (Figures 5b and 6d), the ligand of CCR4, which could recruit CD4 þ Th2 into the lesional sites. 15,16 Therefore, these data collectively indicated that this modified model resembled the Th2-predominant pattern in SSc.…”
Section: Discussionmentioning
confidence: 55%
“…In addition, the expressions of chemokines CXCL2 and CCL17 were shown to be induced in the skin lesion following implantation of minipumps with BLM (Figure 5b), which strongly supported the cellular infiltration of neutrophils and T cells in the skin lesion according to their preferential chemotactic ability. [13][14][15][16] Delivery of BLM by Skin-Embedded Osmotic Minipumps Induces Interstitial Lung Disease-Like Manifestation SSc is a systemic autoimmune disease with multiple organs involved, and ILD is one of the most significant complications in SSc. TGF-b1 is widely considered to have a central role in fibrosis.…”
Section: Delivery Of Blm By Skin-embedded Osmotic Minipumpsmentioning
confidence: 99%
“…In addition, it has recently been reported that CCL22 was a potent and rapid inducer of CCR4 internalization, whereas CCL17 did not induce the same effect. 73 The authors of this study speculate that CCL17's effects may be limited to the endothelial surface where its interaction with CCR4 may be important in vascular recognition whereas CCL22 may exert its major effects within the tissue microenvironment where its interaction with CCR4 guides the localization of various immune cells. 73 Regardless of their exact roles, both chemokines appeared to be important in the egg granulomatous response and thus both chemokines may be important targets in pathological granulomatous responses that exhibit a type-2 cytokine phenotype in the lung.…”
Section: Discussionmentioning
confidence: 87%
“…This review will refer to studies that suggest a role for lipid rafts/caveolae in CCR5 internalization as well as studies that suggest that CCR5 internalization is completely clathrin-dependent. It has also been demonstrated that CCR4 internalization depends on lipid raft integrity and functionality of clathrin-coated pits [45]. These various results may reflect differences in cell type and experimental approach.…”
Section: Introductionmentioning
confidence: 99%